Workability, strength and shrinkage of fiber reinforced expansive self-consolidating concrete. (30th January 2017) - Cao, Qi; Cheng, Yinliang; Cao, Mingli; Gao, Quanqing
Highlights: Effects of fibers on properties of expansive self-consolidating concrete (ESCC) were studied. Workability of fresh concrete decreases with increased volume fraction of fibers. Steel fiber improves the linear load-deflection relationship of ESCC beams. Free expansive rate of ESCC reduces with the increase of steel fibers content. Abstract: A testing program was undertaken to evaluate the effects of fibers on properties of expansive self-consolidating concrete (ESCC). Hooked end steel fibers and monofilament polypropylene fibers were used in the tests with three selected volume fractions (0.25%, 0.50% and 0.75% of the total volume of concrete) for steel fibers and one volume fraction (0.10%) for polypropylene fibers. Workability of fresh concrete, mechanical properties and shrinkage of hardened concrete were investigated. Slump flow, J-ring and V funnel tests were carried out to evaluate the filling ability, passing ability, and viscosity of the fresh concrete. Mechanical properties including compressive strength, splitting tensile strength and flexural strength of hardened concrete were studied. Test results indicate that workability of fresh concrete decreases with increased volume fraction of fibers. The compressive strength of ESCC is improved at 7 days with added expansive admixture. Combined addition of expansive admixture and fibers reduces the concrete strength at 7 days, while it does not influence the 28 days strength noticeably. For flexural performance, steel fiber improves the linear load-deflection relationship of ESCC beams. Steel fiber reinforced beam specimens with fiber content higher than 0.50% show deflection-hardening behavior. It is also found that free expansive rate of ESCC reduces with the increase of steel fibers content. Overall, fiber reinforced ESCC both at 0.25% and 0.50% volume content satisfy the target performance criteria.